ERS statement on exercise training and rehabilitation in patients with severe chronic pulmonary hypertension. Issue 2 (28th February 2019) - Grünig, Ekkehard; Eichstaedt, Christina; Barberà, Joan-Albert; Benjamin, Nicola; Blanco, Isabel; Bossone, Eduardo; Cittadini, Antonio; Coghlan, Gerry; Corris, Paul; D'Alto, Michele; D'Andrea, Antonello; Delcroix, Marion; et al.
Objectives of this European Respiratory Society task force were to summarise current studies, to develop strategies for future research and to increase availability and awareness of exercise training for pulmonary hypertension (PH) patients. An evidence-based approach with clinical expertise of the task force members, based on both literature search and face-to-face meetings was conducted. The statement summarises current knowledge and open questions regarding clinical effects of exercise training in PH, training modalities, implementation strategies and pathophysiological mechanisms. In studies (784 PH patients in total, including six randomised controlled trials, three controlled trials, 10 prospective cohort studies and four meta-analyses), exercise training has been shown to improve exercise capacity, muscular function, quality of life and possibly right ventricular function and pulmonary haemodynamics. Nevertheless, further studies are needed to confirm these data, to investigate the impact on risk profiles and to identify the most advantageous training methodology and underlying pathophysiological mechanisms. As exercise training appears to be effective, cost-efficient and safe, but is scarcely reimbursed, support from healthcare institutions, commissioners of healthcare and research funding institutions is greatly needed. There is a strong need to establish specialised rehabilitation programmes for PH patients to enhance patient access to this treatment intervention. Specialised exercise training in patients with pulmonary hypertension appears to be effective, cost-efficient and safe. More support is necessary from healthcare institutions and politicians to establish such programmes throughout Europe. http://ow.ly/kLvS30mUbja